ANALISIS ISI FILM “EXHUMA” - Aura Julia Azzahra; Farah Shafira, Virgie Suciana Kusuma, Daffa Eka Putri (ADISAM PUBLISHER, 2025)
The development of film has grown rapidly from year to year. Various film themes have been presented as a means of entertainment or to convey messages to people. This research aims to describe the message conveyed in a film by analyzing the content qualitatively in the presentation of the story of the film